Incline wheelchair - Tam, Kwan Yuen (2012)
Medical equipment for the disabled and the elderly today provide limited assistance to the population due to the myriad of illnesses and variety of medical conditions. For instance, wheelchair users vary from spinal cord injuries to muscular dystrophy, which require different equipment to care for their specific needs. In addition, with the increase of the elderly population in the world, more sophisticated and suitable medical equipment need to be developed to meet their needs.